2014
DOI: 10.3389/fnhum.2014.00010
|View full text |Cite
|
Sign up to set email alerts
|

Visual Evoked Potential and Magnetic Resonance Imaging are More Effective Markers of Multiple Sclerosis Progression than Laser Polarimetry with Variable Corneal Compensation

Abstract: Background: The aim of our study was to assess the role of laser polarimetry and visual evoked potentials (VEP) as potential biomarkers of disease progression in multiple sclerosis (MS).Participants: A total of 41 patients with MS (82 eyes) and 22 age-related healthy volunteers (44 eyes) completed the study. MS patients were divided into two groups, one (ON) with a history of optic neuritis (17 patients, 34 eyes) and another group (NON) without it (24 patients, 48 eyes). The MS patients and controls underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…While some studies showed no correlations between evoked potentials and MR imaging, 11 other studies reported significant correlations between VEP and T2 lesion load. 12 However, to the best of our knowledge, a correlation of DTI with VEP has not been published.…”
mentioning
confidence: 99%
“…While some studies showed no correlations between evoked potentials and MR imaging, 11 other studies reported significant correlations between VEP and T2 lesion load. 12 However, to the best of our knowledge, a correlation of DTI with VEP has not been published.…”
mentioning
confidence: 99%
“…Our results showed that the latency was extended and FVEP-P100 amplitude sharply fell in the first day following injury, but maximal recovery was seen with 14 d. FVEP is useful tool for recoding the local responses from visual field defects and can diagnose optic nerve disorders in patients, in conjunction with optical coherence tomography imaging [19]. FVEP is a superior in monitoring the progression optic nerve injury, an provides an accurate estimation of demyelinization and axonal degeneration [20]. Most importantly, in our experimental model of optic nerve injury, protection and functional recovery by NRG-1 treatment was clearly demonstrated by shorter latency and higher FVEP-P100 amplitude.…”
Section: Discussionmentioning
confidence: 84%
“…Özellikle prekiazmatik görme yollarının işlevini değerlendirmede kullanılan önemli bir inceleme yöntemidir (4). Görme keskinliğinin nesnel değerlendirmesi ve ambliyopi izlemi için kullanılabildiği gibi (5), multipl skleroz ya da diğer nedenlere bağlı optik nörit tanısında da sıklıkla kullanılmaktadır (6). Manyetik rezonans görüntüleme ile karşılaştırıldığında daha düşük maliyetli ve daha fazla lezyon saptama oranına sahip olduğu belirtilmiştir (7)(8).…”
Section: Discussionunclassified